2017
DOI: 10.21037/jtd.2017.04.32
|View full text |Cite
|
Sign up to set email alerts
|

Long-term statin therapy could be efficacious in reducing the lipoprotein (a) levels in patients with coronary artery disease modified by some traditional risk factors

et al.

Abstract: Background: Lipoprotein (a) [Lp (a)] is a well-established risk factor for coronary artery disease (CAD).However, up till now, treatment of patients with higher Lp (a) levels is challenging. This current study aimed to investigate the therapeutic effects of short-, medium and long-term statin use on the Lp (a) reduction and its modifying factors. Methods: The therapeutic duration was categorized into short-term (median, 39 days), medium term (median, 219 days) and long-term (median, 677 days). The lipid profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This may be because the animals used in this study were It is currently unclear whether the level of Lp (a), a potent risk factor for heart disease, 33 is suppressed by statins, a widely used class of hydroxymethylglutaryl-CoA reductase inhibitors. [34][35][36] SARM-2f showed a tendency to reduce blood Lp (a) levels in monkeys. Further studies are required to confirm this effect.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This may be because the animals used in this study were It is currently unclear whether the level of Lp (a), a potent risk factor for heart disease, 33 is suppressed by statins, a widely used class of hydroxymethylglutaryl-CoA reductase inhibitors. [34][35][36] SARM-2f showed a tendency to reduce blood Lp (a) levels in monkeys. Further studies are required to confirm this effect.…”
Section: Discussionmentioning
confidence: 95%
“…It is currently unclear whether the level of Lp (a), a potent risk factor for heart disease, is suppressed by statins, a widely used class of hydroxymethylglutaryl‐CoA reductase inhibitors . SARM‐2f showed a tendency to reduce blood Lp (a) levels in monkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, metabolic site and metabolic mechanisms of LP (a) in vivo remain unclear, and racial genetic factors have a greater impact on them. A number of studies have shown that atherosclerotic disease is closely related to LP (a), and LP (a) rise is an independent risk factor for cardiovascular events (Fan et al, 2017, Xu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of statins, there are conflicting findings regarding their effect on Lp(a) levels. Some studies have shown that statins are effective in lowering Lp(a) levels [ 119 , 120 ], while others have indicated an increase in Lp(a) of 10–20% [ 121 , 122 ]. There are also studies showing no effect of statins on Lp(a) levels [ 123 ].…”
Section: Currently Available Therapies Affecting Lp(a) Levelsmentioning
confidence: 99%